Pendugaan Instrusi Air Laut di Sungai - Salamun Salamun (MEDIA KOMUNIKASI TEKNIK SIPIL, 2012)
Estuary is mixing of salt water and fresh water. Therefore Estuary is interisting object to investigation by researcher. Estuary Phenomenon of hydraulic Estuary was dynamic so this research to use numerical model. This model can to be used forecasting for salinity intrution on Estuary or River. Set up model numerical for several variation of Estuary cross section, discharge and tides. Which Saint Venant equation especially on continuity and momentum equation whice is shown water surface (tides) and discharge flow in the river. The result computation then be coupled with the result of dispertion equation. Stability of the scheme was checked with Courant Number and Peclet Number. This Model was verification with electric conductivity (EC).Keywords: tides, dischargePermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3951[How to cite: Salamun, 2006, Pendugaan Instrusi Air Laut di Sungai, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 3, pp. 251-259]